APLIKASI PUPUK ORGANIK PADA TANAMAN CAISIM UNTUK DUA KALI PENANAMAN - Arnis EN Yulian; Murniati '; Fatimah ' (Jurnal Sagu, 2011)
A n experiment was conducted to find out the type of organic manure on growth and production ofcaisin for twice planting. This experiment used a Completely Randomized Design w ith 5 treatments and 4replications. Treatments were tv'pes of organic manure (chicken inaniire. bokashi manure, kascing manure,T K K S compost and tricho compost). The parameters observed include: leaf area, number of leaves andproductivity. The result showed that all organic manure had residue effect. 1'he highest increase In productivityachieved at second planting was for bokashi manure of 96.72% compare to the first planting, but for all theparameters T K K S compost w us better than other organic manure.